Generalized Beauty:Numbers of Digits as 1 at All and Linear Equations - เอี่ยมพันธ์, อัยเรศ (KKU Science Journal, 2013)
The main purpose of this article is to study and find a general form and a relationship between numbers of digits as 1 at all and linear equations which constant is the number of all digit in numbers of digits as 1 at all.